Design and preparation of gradient graphite/cermets self-lubricating composites. Issue 8 (August 2018) - Zhou, Liming; Xiong, Ji; Guo, Zhixing; Ye, Junliu
Abstract: Based on the functionally graded materials (FGMs) design concept, the laminated-graded graphite/cermets self-lubricating composite was prepared to achieve the integration of mechanical properties and lubrication performance of the cermet. The effects of the layer number and thickness of graded structure on residual stresses in the gradient composites were investigated by finite element method (FEM). From the FEM analyses, the optimal gradient structure design was obtained corresponding to the following parameters: the number of graded layers n = 2 and the thickness of graded structure t = 1 mm. According to the optimum design, a graded graphite/cermets self-lubricating material with two layers was fabricated by a typical powder metallurgy technique. Compared with the homogenous graphite/cermets composite, the surface hardness and indentation fracture toughness of graded composite were increased by approximately 15.9% and 6.3%, respectively. The results of X-ray diffraction (XRD) stress measurement identified the existence of residual compressive stress on the surface of graded composite. Additionally, the friction and wear tests revealed that the wear resistance of the graphite/cermets self-lubricating composite was improved significantly via the graded structural design, whereas the coefficient of friction changed slightly.